2015
DOI: 10.5465/amr.2014.0455
|View full text |Cite
|
Sign up to set email alerts
|

Effectuation As Ineffectual? Applying the 3E Theory-Assessment Framework to a Proposed New Theory of Entrepreneurship

Abstract: Effectuation is a proposed new theory of entrepreneurship, with insufficient empirical testing and critical analysis. Drawing on a new, comprehensive set of theory-building criteria-sourced from and complementing those of Robert Dubin and others-we provide the first formal assessment of effectuation as a theory. We highlight its strengths and weaknesses, leveraging the former to address the latter in five different directions that would build on the existing work to improve this theory. The assessment exercise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
220
0
10

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 228 publications
(250 citation statements)
references
References 97 publications
2
220
0
10
Order By: Relevance
“…Although there are still different definitions of and perspectives on effectuation (Arend, Sarooghi, & Burkemper, ; Perry, Chandler, & Markova, ), there are five categories that characterize the effectuation construct: Effectuation is means‐orientated in that it focuses the accumulation of commitments and resources. Actions start with an analysis of the means at hand and an exploration of the possible outcomes that could be reached with those means.…”
Section: Hrd In Entrepreneurs' Firmsmentioning
confidence: 99%
“…Although there are still different definitions of and perspectives on effectuation (Arend, Sarooghi, & Burkemper, ; Perry, Chandler, & Markova, ), there are five categories that characterize the effectuation construct: Effectuation is means‐orientated in that it focuses the accumulation of commitments and resources. Actions start with an analysis of the means at hand and an exploration of the possible outcomes that could be reached with those means.…”
Section: Hrd In Entrepreneurs' Firmsmentioning
confidence: 99%
“…Effectuation theory has not been with criticism. In a recent article by Arend et al (2015) published in the reputed Academy of Management Review, it is suggested that effectuation might be ineffectual as a new theory of entrepreneurship. The key contention is that effectuation has been subjected to insufficient empirical testing and critical analysis.…”
Section: Effectuationmentioning
confidence: 99%
“…A recent controversy has cast doubts about the validity of effectuation as a theory (Arend et al, 2015), but the key supporters of the concept have responded arguing that effectuation has been validated empirically in a considerable number of studies, while also recognizing that the notion is not yet a complete body of knowledge and that further research is still required (Read et al, 2016). Eckhardt and Shane (2003, p. 336) define entrepreneurship as the "discovery, evaluation, and exploitation of future goods and services" and include in the definition the study of opportunities, defined as "situations in which new goods, services, raw materials, markets and organizing methods can be introduced through the formation of new means, ends, or means-ends relationships".…”
mentioning
confidence: 99%
“…: [Arend, Sarooghi, Burkemper, 2015;Eijdenberg, Paas, Masurel, 2015;Politis, Winborg, Dahlstrand, 2012;Smolka et al, 2016]). Эффектуация определена как ло-гика принятия решений на основе име-ющихся в распоряжении ресурсов и вы-бора из возможных результатов тех, ко-торые могут быть достигнуты с помощью этого набора ресурсов.…”
unclassified
“…: [Gabrielsson, Politis, 2011;Politis, Winborg, Dahlstrand, 2012]). Так, в работе [Arend, Sarooghi, Burkemper, 2015] отмечены два основных фактора, оказывающих воздействие на формиро-вание эффектуации: высокая степень не-определенности и ограниченность ресур-сов, доступных предпринимателю. В то же время, помимо индивидуальных фак-торов, на предпринимательское мышле-ние существенное влияние могут оказы-вать факторы внешней среды.…”
unclassified